2016
DOI: 10.1007/s12020-016-1011-9
|View full text |Cite
|
Sign up to set email alerts
|

Omarigliptin for the treatment of type 2 diabetes

Abstract: Omarigliptin is a new once-weekly dipeptidyl peptidase-4 (DPP-4) inhibitor developed for the treatment of type 2 diabetes. It is indicated to have favorable effects on glycosylated hemoglobin (HbA), fasting and postmeal plasma glucose. It potently but reversibly inhibits DPP-4 enzyme, which prolongs the circulating half-life of glucagon-like peptide-1 that increases insulin secretion in a glucose-dependent manner. Benefiting from glucose-dependent insulin secretion, omarigliptin is associated with low risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Gliptins are considered to be effective agents for the treatment of type 2 Diabetes Mellitus. Omariglitpin (OTN), Figure 1 , is a long-acting once weekly administered antidiabetic drug acting as dipeptidyl peptidase-4 (DPP-4) inhibitor [ 5 , 6 , 7 ]. It has been licensed for use in Japan since 2015 but its phase III development in US has been halted for undisclosed commercial reasons [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gliptins are considered to be effective agents for the treatment of type 2 Diabetes Mellitus. Omariglitpin (OTN), Figure 1 , is a long-acting once weekly administered antidiabetic drug acting as dipeptidyl peptidase-4 (DPP-4) inhibitor [ 5 , 6 , 7 ]. It has been licensed for use in Japan since 2015 but its phase III development in US has been halted for undisclosed commercial reasons [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include the dipeptidyl peptidase‐4 (DPP‐4) inhibitors, of which Omarigliptin (OMG) is a once weekly version . In contrast to the once‐daily DPP‐4 inhibitors, once‐weekly OMG can improve patients’ adherence and thus achieve optimal therapeutic efficacy . OMG inhibits DPP‐4 to increase incretin levels (GLP‐1 and GIP) which inhibit glucagon release leading to increase in the insulin secretion and decrease in blood glucose levels with added benefits over currently commercially available DPP‐4 inhibitors with excellent pharmacokinetic profile amenable for once‐weekly human dosing .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the once‐daily DPP‐4 inhibitors, once‐weekly OMG can improve patients’ adherence and thus achieve optimal therapeutic efficacy . OMG inhibits DPP‐4 to increase incretin levels (GLP‐1 and GIP) which inhibit glucagon release leading to increase in the insulin secretion and decrease in blood glucose levels with added benefits over currently commercially available DPP‐4 inhibitors with excellent pharmacokinetic profile amenable for once‐weekly human dosing . OMG (Figure ), is a small‐molecule developed by Merck in Japan and it was generally well‐tolerated with a low incidence of symptomatic hypoglycemia …”
Section: Introductionmentioning
confidence: 99%
“…It was approved in Japan in 2015 and phase Ⅲ clinical trial had completed (Chen et al, 2015a). Compared to once-daily DPP-4 inhibitor (sitagliptin, linagliptin, vildagliptin, saxagliptin and alogliptin), omarigliptin is more potent to inhibit DPP-4 enzyme (Tan, 2016). Previous study of pharmacokinetics and pharmacodynamics in health subject showed that omarigliptin was supportive of a sustained and clinically meaningful effect; it enhanced medication persistence and adherence of patients, optimized glycemic control and also reduced the risk of complications (Krishna et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviations used: DPP-4, dipeptidyl peptidase-4; ESI, electrospray ionization; IS, internal standard; LC-MS/MS, liquid chromatography-tandem mass spectrometry; LLOQ, lower limit of quantification; QC, quality control; RE, relative error; RSD, relative standard deviation; T2DM, type 2 diabetes; UHPLC, ultra-high pressure liquid chromatography enzyme (Tan, 2016). A previous study of pharmacokinetics and pharmacodynamics in healthy subjects showed that omarigliptin was supportive of a sustained and clinically meaningful effect; it enhanced medication persistence and adherence of patients, optimized glycemic control and reduced the risk of complications (Krishna et al, 2016).…”
Section: Introductionmentioning
confidence: 99%